Kualitas Tidur Dengan Keteraturan Siklus Menstruasi Pada Remaja Putri Di SMA X Jakarta - Popi Meykuri; Roza Indra Yeni (Akademi Keperawatan Yarsi Samarinda, 2026)
The menstrual cycle is a physiological process in women that is influenced by the interaction of reproductive hormones with a normal range of 21–35 days. Menstrual cycle disorders are still common in adolescents and can be influenced by various factors, one of which is sleep quality. This study aims to determine the relationship between sleep quality and menstrual cycle regularity in female adolescents at SMA Negeri X Jakarta. This study used an analytical design with a cross-sectional approach. The research sample consisted of 58 respondents. Data collection was carried out through a questionnaire on sleep quality and menstrual cycle regularity. Data analysis used univariate tests to see the frequency and percentage distribution, and bivariate tests using Chi-Square with a significance level of 0.05. Results Poor sleep quality: 47 (87.0%) experienced disturbances and 7 (13.0%) did not experience disturbances. Good sleep quality: 1 (25.0%) experienced disturbances and 3 (75.0%) did not experience disturbances. The test results showed a p-value of 0.14 (>0.05), OR 20.143 with a 95% CI of 1.830–221.690, indicating no significant relationship, but there was a tendency for a higher risk of poor sleep quality. The conclusion of this study is that there is no significant relationship between sleep quality and menstrual cycle regularity, but there is a tendency for an increased risk of menstrual cycle disorders in adolescents with poor sleep quality.